Oxygen-Helium Gas Mixture «Heliox» for the Treatment of Respiratory Failure in Patients with New Coronavirus Infection Covid-19 (Randomized Single-Center Controlled Trial) - R. E. Lakhin; A. D. Zhdanov; A. V. Shchegolev; K. V. Zhdanov; V. V. Salukhov; D. P. Zverev; K. V. Kozlov (Неотложная медицинская помощь)
Introduction. Treatment of respiratory failure in pneumonia caused by coronavirus infection (COVID-19) is still an unsolved problem that requires a comprehensive approach and the development of new methods that expand the range of possibilities of modern therapy. There is evidence that the heated oxygenhelium mixture has a positive effect on gas exchange in the infiltration zone by improving both ventilation and diffusion.AIM of study. To evaluate the effectiveness of the inclusion of a heated oxygen-helium mixture HELIOX (70% Helium/ 30% Oxygen) in the complex intensive care of respiratory failure of pneumonia caused by SARS-CoV-2 infection.Material and methods. The study included 60 patients with confirmed viral pneumonia caused by COVID-19. The patients were randomized into two groups: group 1 (n=30) — patients who were treated with the standard COVID-19 treatment protocol with the heated oxygen-helium mixture HELIOX, and group 2 (control) (n=30) — patients who received standard therapy. Lethality was studied for 28 days, the time in days until a steady increase in SpO2>96% was achieved when breathing atmospheric air; the time until the patient is transferred from the intensive care unit (ICU) to the general department.Results. Inhalation of the HELIOX mixture (70% Helium / 30% Oxygen) resulted in a faster recovery of the hemoglobin oxygen saturation index (SpO2). Starting from day 3, these differences became statistically significant. The time in days from inclusion in the study to a persistent increase in the degree of oxygen saturation of hemoglobin (SpO2>96%) when breathing atmospheric air in the group with inhalation of the HELIOX mixture was less — 8 (7; 10), compared to 10 (8;13) in the control group (p=0.006). In the group with inhaled HELIOX mixture, the median treatment time in the ICU was 8 (7; 9.5) days vs 13 (8; 17) days (p<0.001) in the comparison group.Conclusions. Inhalation of the HELIOX mixture (70% Helium / 30% Oxygen) led to a faster recovery of the hemoglobin oxygen saturation index SpO2, which contributed to reduction in the duration of oxygen therapy and a decrease in mortality.